Hierarchical micro/nanostructures generated by femtosecond laser beams modified through a liquid-crystal spatial light modulator - Chen, Yuan-Di; Tsai, Wu-Jung; Liu, Sung-Ho; Horng, Ji-Bin (Applied surface science, 2015)
•The hierarchical micro/nanostructures inside various shapes can be created using a femtosecond laser machining system with a liquid-crystal spatial light modulator.•Hierarchical micro/nanostructures are composed of micro-sized valley structures of 30μm spacing and nanostrucutres with a periodicity of approximately 400nm.•The orientation of the inner valley structures in the produced hierarchical micro/nanostructures can be selected by changing the azimuth of the pattern beams in the focal plane. The speckle effect, generated by a liquid-crystal spatial light modulator (LCSLM), is studied using a femtosecond laser machining system. The speckle effect of the patterned beams produces hierarchical micro/nanostructures on the surface of polished stainless steel (SS 316L). The results show that the hierarchical micro/nanostructures are composed of micro-sized valley structures created by the LCSLM and nano-sized periodic structures induced by the femtosecond laser. By varying the azimuth of the pattern beams in the focal plane, the directions of the inner valley structures can be altered. As a result of these patterned beams with the speckle effect, the fabrication of hierarchical micro/nanostructures structures inside various shapes becomes a simple one-step procedure instead of a complex scanning process. These hierarchical micro/nanostructures can provide advantages for anti-friction, hydrophobic, and hydrophilic applications in surface treatment.